Physically active individuals have a 23% lower risk of any colorectal neoplasia and a 27% lower risk of advanced colorectal neoplasia than their non-active counterparts: systematic review and meta-analysis of observational studies. Issue 10 (11th July 2019) - Wang, Jingjing; Huang, Liwen; Gao, Yang; Wang, Yanhong; Chen, Shanquan; Huang, Junjie; Zheng, Wenjing; Bao, Pingping; Gong, Yangming; Zhang, Yanfeng; Wang, Mei; Wong, Martin Chi Sang
Abstract : Background: Few studies have examined the associations between physical activity (PA), sedentary behaviour (SB) and risk of colorectal neoplasia (CN). Methods: We systematically searched Medline, Embase, PsyInfo, Cochrane and other sources from their inception to 30 September 2018 for cohort, case-control and cross-sectional studies that evaluated these associations in asymptomatic, average-risk subjects. Random-effect models were used to estimate relative risks (RRs) of any-type CN, advanced CN, and non-advanced CN, respectively, in individuals with the highest versus the lowest level of PA and SB. Dose-response analyses and subgroup analyses were conducted. The I 2 statistic was used to examine heterogeneity among studies. Results: We identified 32 observational studies, including 17 cross-sectional studies, 10 case-control studies and five longitudinal studies. PA (highest vs lowest) was inversely associated with risk for any-type CN (n=23 studies) and advanced CN (n=15 studies), with a RR of 0.77 (95% CI=0.71 to 0.83, I 2 =57.5%) and 0.73 (95% CI=0.63 to 0.82, I 2 =45.5%), respectively. There was no association between PA and non-advanced CN (n=5 studies). There was an as association between PA and any-type CN in both sexes, and also for the distal colon. We found no dose–response relationship between PA and any-type or advanced CN. Based on three studies identified, SB time (longest vs shortest) was associated with an increased risk of advanced CN (RR=1.24, 95% CI 1.04 to 1.49, I 2 =14.4%). No publication bias was detected by Begg's test. Conclusion: We report a 23% lower relative risk of any type of CN and a 27% lower risk of advanced CN in people with the highest level of PA compared with those in the lowest.